Satisfaction With Elbow Function and Return Status After Autologous Osteochondral Transplant for Capitellar Osteochondritis Dissecans in High School Baseball Players. Issue 12 (October 2020) - Sasanuma, Hideyuki; Iijima, Yuki; Saito, Tomohiro; Yano, Yuichiro; Nakama, Sueo; Kameda, Masahiro; Takeshita, Katsushi
Background: Osteochondral autograft transplant (OAT), a surgical treatment for capitellar osteochondritis dissecans (OCD), has favorable rates of elbow recovery and return to sports in adolescents. However, few reports have investigated how long patients continue to play baseball after OAT and their satisfaction with their treatment outcome. Purpose: To evaluate the rate of boys who played baseball and received OAT for OCD in junior high school or earlier (age <15 years) and continued to play baseball in high school and the players' satisfaction with their elbow function during play. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 32 elbows of boys who played baseball and received OAT at age ≤15 years (mean, 14.1 years) were examined and divided into pitcher (n = 11) and nonpitcher (n = 21) groups according to their player position before surgery. The clinical Timmerman-Andrews score at the end of their high school baseball, participation percentage of players who continued to play baseball, and satisfaction level during play (on a scale of 0-10 during pitching and batting and in a 4-choice format) were compared between the 2 groups. Results: The Timmerman-Andrews scores significantly improved after surgery in both groups, with no significant difference between the groups. Of the 32 players, 30 (93.8%) continued to play baseball throughout high school, including all players in the pitcher group and 19 (90.5%) of those in the nonpitcher group. The percentage of players who continued to pitch was 55.6% (6/11) in the pitcher group. Satisfaction with elbow joint function at the time of pitching was significantly lower in the pitcher group. Further, 5 players reported being "a little unsatisfied" because of elbow pain during pitching. All of the players indicated satisfaction with elbow function during batting. Conclusion: The percentage of players who received OAT for OCD in junior high school and continued to play baseball in high school was favorable. However, satisfaction with elbow function during throwing was lower in pitchers than in nonpitchers. Clinical Relevance: Before surgery, consent should be obtained from patients who are pitchers after it is explained that satisfaction with elbow joint function during pitching could be decreased after OAT.